Enhancing Traffic Management in Lahore: A Comprehensive Analysis of Drivers’ Perspectives on Interactions with City Traffic Police - Talha , Nighat; Iqbal, Shahzaf; Manan, Syed Abdul (Pakistan Journal of Humanities and Social Sciences, 2023)
The purpose of this study is to investigate the challenges faced by drivers while interacting with City Traffic Police (CTP) in Lahore, Pakistan. CTP plays a vital role in maintaining traffic flow and improving road safety. The study used a mixed methods approach, combining qualitative interviews using Critical Incident Techniques (CIT) to explore issues, affinity diagrams for thematic analysis, and frequency analysis to quantitatively identify the most important transportation issues based on their occurrence. The study identified 32 different traffic problems and classified them into four categories of drivers. Thematic analysis reveals eight overarching themes, including road conditions, behavioral issues of traffic police, license issuance hurdles, traffic tickets and challans, grievance redressal procedures, signal malfunctions, discriminatory conduct, and corruption within the CTP domain. Quantitative analysis highlights road conditions, behavioral issues, and license-related problems as the most frequently reported concerns. Theoretical implications draw on Social Exchange Theory (SET) to analyze drivers' interactions, emphasizing the pivotal role of trust in shaping satisfaction and compliance. Practical implications urge policymakers to prioritize road maintenance, enhance communication skills of traffic wardens, and address corruption and discrimination for improved traffic management. Limitations include potential bias from convenience sampling, reliance on subjective recollections in CIT, and the study's exclusive focus on drivers. Recommendations for future research advocate rigorous sampling methods, broader geographical scope, diverse stakeholder involvement, and the incorporation of quantitative surveys.